Sensitivitas Gender dalam Putusan Hakim Perkara Pembagian Harta Bersama di Pengadilan Agama Purwokerto dan Banyumas - Utami, Pangestika Rizki; Cahyani, Indah Dwi (RIO LAW JURNAL, 2024)
The discussion about gender is interesting to discuss, because later it will refer to two divisions namely; gender sensitivity or gender bias. This study tries to explore and analyze gender sensitivity through several decisions of religious court judges whether in legal considerations the judges are gender sensitive or gender biased, and in this study researchers seek to find out the implementation of PERMA Number 3 of 2017 in implementation at the Purwokerto and Banyumas Religious Courts through interviews with the judge examining the case, especially in cases of distribution of joint assets. In the decisions of the Purwokerto and Banyumas Religious Courts which will become the object of research, through a study of decisions in the legal considerations of the judges of each court and how the implementation of PERMA number 3 of 2017. This research uses empirical normative research methods through a qualitative juridical approach where researchers conceptualize law as a normative system, namely through library research (library reasearch) using additional data in the form of direct interviews with research respondents. Based on legal considerations, several decisions of the Purwokerto Religious Court were in accordance with existing regulations and the case examining judge was gender sensitive, but in several cases the division of assets with the woman who filed the lawsuit was a housewife. Whereas in the decision of the Banyumas Religious Court based on the judge's legal considerations there was a decision that the judge in deciding to consider the distribution of joint assets based on sharing during marriage by proving it in the Decision which stated that women are entitled to more than half of the distribution of joint assets this is based on the Jurisprudence of Cassation Decision Number 266K /AG/2010 which deviates from the provisions of Article 97 KHI as a formal legal principle, but judges as law makers (judge made law) must be more observant in seeing the basics of justice in accordance with the principle of justice and the principle of proportional balance.